The fabrication of formamidinium lead iodide perovskite thin films via organic cation exchange. Issue 19 (12th February 2016) - Zhou, Zhongmin; Pang, Shuping; Ji, Fuxiang; Zhang, Bo; Cui, Guanglei
Abstract : With NH4 PbI3 as the starting material, an organic cation exchange concept is employed to fabricate high-quality α-FAPbI3 perovskite thin films. Abstract : High-quality formamidinium lead iodide (FAPbI3 ) perovskite thin films are fabricated via organic cation exchange. With ammonia lead iodide (NH4 PbI3 ) as the starting material, the NH4 + in NH4 PbI3 could be gradually substituted by FA + in formamidine acetate (FA-Ac) and simultaneously transformed to the pure phase α-FAPbI3 at elevated temperature.